Management of necrotizing pancreatitis and its outcome in a secondary healthcare institution - Karim, Tanweer; Kumar, Vinod; Katiyar, Vivek Kumar; K., Subhash (International Surgery Journal, 2017)
Background: Surgical debridement is the “gold standard” for infected pancreatic necrosis. Advances in imaging methods and minimal access techniques have changed the management of many surgical conditions and even infected pancreatic necrosis has successfully been treated in selected patients. However, technical advances don’t obviate sound clinical judgment. Aim was to consider recent advances in minimal access surgery, this article retrospectively analyses the role of open surgery and laparoscopic techniques in the management of necrotizing pancreatitis. Methods: A retrospective study of 30 cases of pancreatic necrosectomy admitted and managed during 2012-2016 was carried out and compared with results available in the existing literature. Results: Out of 30 cases, 20 were men and 10 were women. Patients’ age ranged from 23 to 70 years (mean age - 49.8 years). The mean operating time was 103.8 min (range, 60-120 min). Timing of necrosectomy was 21-32 days (average - 25.5 days). The average duration of hospital stay after the procedure was 17.4 days (range, 10-21 days). Conclusions: Comparative analysis of results of different surgical techniques reveals that there is no significant difference in terms of mortality. However, overall rate of complications and failure (inadequate debridement and drainage) are still higher with minimally invasive techniques.